2015
DOI: 10.1007/s13131-015-0697-2
|View full text |Cite
|
Sign up to set email alerts
|

Runout prediction and dynamic characteristic analysis of a potential submarine landslide in Liwan 3-1 gas field

Abstract: A large number of submarine landslides with different scales have been identified in the canyon area of the submarine pipeline route of Liwan 3-1 gas field. There is still much chance that submarine slope failures would happen, and the following mass movement would present great risk to the submarine pipeline. In view of this, a numerical prediction method based on Eulerian-Eulerian two-phase flow model is introduced to simulate the mass movement of potential submarine landslides. The sliding soil and ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Figures 9 and 10 show the Tresca stress and velocity distributions at different time points, respectively, in the case of S um = 5 kPa, K = 1.15 kPa/m, and S t = 4.0. It can be seen that both cases show a shallow landslide failure mode, which is consistent with the stability analysis of the submarine slope and the geophysical interpretation of existing landslide characteristics [16,[40][41][42]45]. In the case that the initial stress has not been taken into account, the self-weight load can lead to large fluctuations in the stress field.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Figures 9 and 10 show the Tresca stress and velocity distributions at different time points, respectively, in the case of S um = 5 kPa, K = 1.15 kPa/m, and S t = 4.0. It can be seen that both cases show a shallow landslide failure mode, which is consistent with the stability analysis of the submarine slope and the geophysical interpretation of existing landslide characteristics [16,[40][41][42]45]. In the case that the initial stress has not been taken into account, the self-weight load can lead to large fluctuations in the stress field.…”
Section: Resultssupporting
confidence: 84%
“…Multibeam topography has shown that the heights of the landslide scarps, which are mainly located at the sidewall and the interfluve of the canyon, are basically between 8 and 125 m, and the maximum local slope can reach 26.6 • [43]. The soil in the Shenhu sea area has medium or high soil sensitivity based on the drilling test and the in situ CPT test [44,45], and the undrained shear strength exhibits linear and segmented linear growth with increasing burial depth. The intact undrained shear strength of the soil, S u0 , can be expressed as…”
Section: Engineering Geological Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential threat of submarine slides on offshore infrastructures, such as submarine pipelines, has recently received much attention (e.g. Locat and Lee 2002;Wang and Miao 2008;Zakeri et al 2008Zakeri et al , 2009Zhu and Randolph 2010;Randolph and White 2012;Sahdi et al 2014;Yuan et al 2014;Liu et al 2015;Xiu et al 2015;Dong et al 2017;Nian et al 2018;Dutta and Hawlader 2019;Guo et al 2019;Zhang et al 2019;Fan et al 2019;Qian et al 2020), to ensure safe offshore developments. In particular, there have been a number of specialized international research initiatives [e.g.…”
mentioning
confidence: 99%